Effect of crude Ganoderma applanatum polysaccharides as a renoprotective agent against carbon tetrachloride-induced early kidney fibrosis in mice - Raden Joko Kuncoroningrat Susilo; Dwi Winarni; Suhailah Hayaza; Ruey-An Doong; Sri Puji Astuti Wahyuningsih; Win Darmanto (Veterinary World, 2022)
Background and Aim: Interstitial fibrosis is the final stage of chronic kidney injury, which begins with an inflammatory process. Crude Ganoderma applanatum polysaccharides are known to have anti-inflammatory properties. The potential role of crude G. applanatum polysaccharides in renal fibrosis through pro-inflammatory cytokines needs further investigation. This study aimed to determine the renoprotective effect of crude G. applanatum polysaccharide extract in mice with carbon tetrachloride (CCL4)-induced early kidney fibrosis.